The True Host/s of Picobirnaviruses - Ghosh, Souvik; Malik, Yashpal S. (Frontiers in Veterinary Science, 2021)
Picobirnaviruses (PBVs) are bisegmented double-stranded RNA viruses that have been detected in a wide variety of animal species including invertebrates and in environmental samples. Since PBVs are ubiquitous in feces/gut contents of humans and other animals with or without diarrhea, they were considered as opportunistic enteric pathogens of mammals and avian species. However, the virus remains to be propagated in animal cell cultures, or in gnotobiotic animals. Recently, the classically defined prokaryotic motif, the ribosomal binding site sequence, has been identified upstream of putative open reading frame/s in PBV and PBV-like sequences from humans, various animals and environmental samples, suggesting that PBVs might be prokaryotic viruses. On the other hand, based on the detection of some novel PBV-like RNA-dependent RNA polymerase sequences that use the alternative mitochondrial genetic code (that of mold or invertebrates) for translation, and principal component analysis of codon usage bias for these sequences, it has been proposed that PBVs might be fungal viruses with a lifestyle reminiscent of mitoviruses. These contradicting observations warrant further studies to ascertain the true host/s of PBVs, which still remains controversial. In this minireview, we have focused on the various findings that have raised a debate on the true host/s of PBVs.